Interelasi Tradisi-Modernisasi pada Masyarakat Towuti Kabupaten Luwu Timur - Sam'un Mukramin; Suardi Suardi (Universitas Muhammadiyah Makassar, 2017)
This research is based on the change of tradition in Towuti society more on the lifestyle of city society or westland culture. But the problem is the relationship and the impact that occurs due to the interrelation of tradition-modernization. This research is a content analysis research. This type of research is a type of qualitative data type. Qualitative data include the condition of the research area and the physical aspects of the research area. Data were collected using observation, literature review and documentation study. The analysis method used is the analysis of overlay and descriptive analysis. The informants were determined purpusive sampling. Data collection techniques are observation, documentation, interview. Data analysis techniques through various stages of data reduction, data presentation and conclusion, while the technique of data validity using source triage, time and technique. The results of this study indicate that, (i) relationships that occur between communities are still good although there have been changes little by little. (ii) the impact of adopting a society that upholds tradition and modern society with various changes.Keywords: Society, Traditional, Modernization.